PERLINDUNGAN ANAK DARI PERKAWINAN SIRI BERDASARKAN PASAL 20 UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Supomo, Aris (Universitas Wiralodra, 2017)
By the presence of a child born from a legal marriage (marriage recorded) both of his parents have proven that the child is a legitimate biological child of his father and mother. The legal consequences if the marriage is not recorded (generally known as